ANALYSIS OF THE EFFECT OF MURABAHA FINANCE IN SHARIA BANKS ON THE ECONOMIC GROWTH OF AGRICULTURAL SECTOR - Siti Afidatul Khotijah; Chaidir Iswanaji (Univeristas Islam Bandung, 2020)
The purpose of this study is to analyze the influence of Islamic banks murabaha financing on the economic growth of the agricultural sector which measured by Gross Domestic Product (GDP) of the agricultural sector and analyze the characteristics of murabaha for the agricultural sector. The analytical method used is simple linear regression and also a qualitative overall analysis. Data analyzed from 2010-2018 were 36, obtained from the Otoritas Jasa Keuangan (OJK) and Badan Pusat Statistik (BPS). The results showed that murabaha financing had a positive effect on economic growth in the agricultural sector. Murabaha products in Islamic banking are one of the easiest products to use as an alternative to financing the agricultural sector. Because of its simplicity, this product has become more frequently used and most of the distribution of funds is through murabaha contracts. Even so the murabaha scheme of the agricultural sector has different characteristics from other sectors, considering that farmers can only pay the installments after the harvest. That way, Islamic banking must have the right source of funds for this financing, such as mudharabah muqayyadah. Not all agricultural financing activities must use the murabaha contract, because in its application it must also be adjusted to the terms and funding period, so Islamic Banks can use alternative contracts that are more appropriate.